ACM's Annual Report. - Hall, Wendy (Communications of the ACM, 2010)
The article discusses the activities of the Association for Computing Machinery in the 2009 fiscal year. The year 2009 was the 10th year that the Association for Computing Machinery's (ACM) Digital Library has been operational and it has over 240,000 full-text articles available, 22,000 of which were added in 2009. ACM is the publisher of 78 periodicals which includes 6 journals and 23 newsletters. ACM entered into an educational partnership with WGBH Educational Foundation on the project "New Image of Computing" in 2009.